Albert S. Lindeman, A History of European Socialism, New Haven—London,Yale University Press 1983, ss. 385 - Czarnota, Adam (Czasopismo Prawno-Historyczne, 1984)
Recenzja: Albert S. Lindeman, A History of European Socialism, New Haven—London,Yale University Press 1983, ss. 385.